Long-term performance of mechanically post-installed anchor systems. Issue 3 (March 2017) - Kwon, Minho; Kim, Jinsup; Seo, Hyunsu; Jung, Wooyoung
A mechanically post-installed anchor, which is one of the most widely used post-installed anchors in South Korea, was selected to evaluate long-term usage through a pullout test. Two types of specimens were constructed: the original specimens and freeze and thaw specimens. Mechanically post-installed anchors were installed in both of them. A freeze and thaw test method was utilized to consider the long-term usage. The compressive strength of concrete during the freeze and thaw test method is reduced by about 20% compared to that of the original concrete. From the pullout test results, the pullout strength of the freeze and thaw specimen was smaller by about 50% than that of the original specimens. Furthermore, the failure mode of the freeze and thaw specimens was changed. Cone shape destruction of anchors and anchor pullout destruction occurred in the original specimens; concrete pullout destruction occurred dominantly in the freeze and thaw specimens. Based on the comparison results, the reduction factor ( λ ) for long-term usage of the mechanically post-installed anchor was derived using a probability function and was proposed to modify the concrete capacity design equation.